Réponses

2014-02-07T17:10:49+01:00
Bonjour,

a = 3(x - 2) + 5(3 - x)
   = 3x - 6 + 15 - 5x
   = -2x + 9

b = x(3 + x) - 2(x + 5)
   = 3x + x² - 2x - 10
   = x² + x - 10

c = -2(x - 7) - 2(x² + x) + 4(x² + 1)
   = -2x + 14 - 2x² - 2x + 4x² + 4
   = 2x² - 4x + 18

d = 2x(-x + 5) - x²(1 - x)
   = -2x² + 10x - x² + x^3
   = x^3 - 3x² + 10x

e = -6x(2x² - 3x) - 3(x + 4x²) - x(-3 + 4x)
   = -12x^3 + 18x² - 3x - 12x² + 3x - 4x²
   = -12x^3 + 2x² 
2014-02-07T18:54:18+01:00
A = 3(x - 2) + 5(3 - x) =
3x - 6 + 15 - 5x =
-2 x + 9
B = x(3 + x) - 2(x + 5) =
3x + x² - 2x - 10 =
x² + x - 10
C = -2(x - 7) - 2(x² + x) + 4(x² + 1) 
-2x + 14 - 2x² - 2x + 4x² + 4 =
2 x² - 4x + 18
D = 2x(-x + 5) - x²(1 - x) =
-2x² + 10x - x² + x^3 =
x^3 - 3 x² + 10x
E = -6x(2x² - 3x) - 3(x + 4x²) - x(-3 + 4x)=
-12x^3 + 18x² - 3x - 12x² + 3x - 4x²=
-12 x^3 + 2x²